Forest and floods: Moving to an evidence-based approach to watershed and integrated flood management - Calder, I.R.C.; Aylward, B. (2006)
Evidence is presented to show that there is a growing disparity between public perception and scientific evidence relating to the causes of floods, their impacts, and the benefits of mitigation measures. It is suggested that this disparity has arisen through the extensive promotion of certain land uses and engineering interventions by vested interest groups in the absence of any effective dissemination of the scientific evidence which may allow a contrary view. It is believed that this disparity may have resulted not only in the wastage of development funds (possibly to the extent of tens of billions of dollars per year) on unachievable targets, but also in the unwarranted blame of upland communities whose practices have generally had only marginal impacts on downstream flooding. It is recognized that the interaction of floods and society is a highly complex subject. What is recognized, with some certainty, is that simplistic and populist land management solutions, such as oft-advocated solutions involving commercial afforestation programs, cannot ever represent a general solution and will, in most situations, have at best marginal benefit and at worst negative impacts. Similarly, structural engineering interventions, although in the short term providing protection to flood-affected communities in one area may have the effect of transferring the problem downstream and may also introduce other unforeseen adverse environmental and economic impacts. An improved approach to watershed and flood management is proposed that integrates watershed and land-use management in the highlands with land-use planning, engineering measures, flood preparedness, and emergency management in the affected lowlands while taking into account the social and economic needs of communities in both the highland, often source areas, and also the lowland flood-prone affected communities. This approach should be based on our best available scientific knowledge of the causes and the environmental, social, and economic impacts of floods and the environmental, social, and economic effects of engineering interventions.